p ( x ) = x 2 0 1 1 + n = 1 ∑ 2 0 1 0 a n x 2 0 1 1 − n + 1
Let x 1 , x 2 , x 3 , x 4 , ⋯ , x 2 0 1 1 be the roots of the monic polynomial above and let y 1 , y 2 , y 3 , y 4 , ⋯ , y 2 0 1 1 be defined as:
y 1 y 2 y 3 ⋮ y 2 0 1 0 y 2 0 1 1 = x 1 x 2 x 3 . . . x 1 0 = x 2 x 3 x 4 . . . x 1 1 = x 3 x 4 x 5 . . . x 1 2 = ⋮ = x 2 0 1 0 x 2 0 1 1 x 1 . . . x 8 = x 2 0 1 1 x 1 x 2 . . . x 9
If the value of ( y 1 y 2 y 3 . . . y 2 0 1 1 ) 2 0 1 1 2 0 1 0 can be expressed as lo g 1 0 a . Find a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is an overrated question
But still it was a good one.
Log in to reply
I know this is a simple problem. At first glance, I too thought of it as a problem that was gonna take a lot of paperwork but when I found the way to solve this, I was laughing at myself that I was thinking so much for a simple problem only because it was constructed so well.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Vieta's Formula - Higher Degrees
From p ( x ) , we get,
i = 1 ∏ 2 0 1 1 x i = − 1 Using Vieta’s formulas
We observe that,
( y 1 ⋅ y 2 ⋅ y 3 . . . y 2 0 1 1 ) = x 1 ⋅ x 2 ⋅ x 3 . . . x 2 0 1 1 1 0 = ( i = 1 ∏ 2 0 1 1 x i ) 1 0 = ( − 1 ) 1 0 = 1
Hence,
( y 1 ⋅ y 2 ⋅ y 3 . . . y 2 0 1 1 ) 2 0 1 1 2 0 1 0 = ( 1 ) 2 0 1 1 2 0 1 0 = 1
And,
lo g 1 0 a = 1 ⟹ a = 1 0